2009
DOI: 10.1007/s12017-009-8084-z
|View full text |Cite
|
Sign up to set email alerts
|

Manganese and its Role in Parkinson’s Disease: From Transport to Neuropathology

Abstract: Abstract:The purpose of this review is to highlight recent advances in the neuropathology associated with Mn exposures. We commence with a discussion on occupational manganism and clinical aspects of the disorder. This is followed by novel considerations on Mn transport (see also chapter by Yokel, this volume), advancing new hypotheses on the involvement of several transporters in Mn entry into the brain. This is followed by a brief description of the effects of Mn on neurotransmitter systems that are putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 122 publications
1
56
0
Order By: Relevance
“…Non-motor symptoms have also been associated with excessive Mn exposure (Guilarte et al, 2008b;Aschner et al, 2009;Guilarte, 2013). Neuropathological changes in frontal cortex of non-human primates as a consequence of Mn exposure have also been described (Verina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Non-motor symptoms have also been associated with excessive Mn exposure (Guilarte et al, 2008b;Aschner et al, 2009;Guilarte, 2013). Neuropathological changes in frontal cortex of non-human primates as a consequence of Mn exposure have also been described (Verina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Mn-ions were found to protect against the Shiga toxin in mice by redirecting it to the degradative pathway [161,162], but no protection was provided against Stx2 under the same conditions [163]. Also, protection against Shiga toxins may depend on cell type and the mouse strain [164], and caution should be exerted since Mn-ions are neurotoxic [164,165]. Quite recently, chemical compound screens have provided us with drugs that seem to inhibit endosome-to-Golgi transport and that protect against both the plant toxin ricin and Shiga toxin [166][167][168].…”
Section: Protection Against Shiga Toxinsmentioning
confidence: 99%
“…It is of interest that the clinical effects of Mn neurotoxicity resemble Parkinson's disease (Aschner et al, 2009). In this respect, it has been shown that a rare variant of the hGDH2 gene leads to earlier age of onset in Parkinson's disease patients (Plaitakis et al, 2010).…”
Section: Article In Pressmentioning
confidence: 99%